Complications of augmentation procedures for dental implants in private practice, Victoria, Australia. (27th May 2019) - Dastaran, M; Bailey, D; Austin, S; Chandu, A; Judge, R
Abstract: Purpose: This study audited complications associated with augmentation for dental implants, retrospectively over a 5‐year period in a variety of private dental practices in Victoria (Australia). Methods: Complications were categorized as surgical or biological and compared to a group not requiring augmentation. Implant factors underwent univariate and multivariate analysis. Results: The study assessed 8486 implants with 26.9% undergoing augmentation. Augmentation had no effect on implant survival, however, a significant increase in complications for those implants requiring augmentation was found ( P = <0.001). The hard tissue augmented group had significantly more cases of insufficient bone/dehiscences at implant placement ( P < 0.001), and post‐placement bone loss ( P = 0.0014). These implants were grafted simultaneously ( P < 0.05) with particulate autogenous bone and/or Bio‐Oss ( P < 0.05) with resorbable xenograft membrane ( P < 0.001). There was significantly more bone loss in open sinus lifted cases than implants placed in native bone (1.90% v 0.30%; P = 0.009). Conclusions: The study demonstrated no increase in graft complications that could be related to any specific augmentation technique, suggesting that routine grafting procedures used in private practice were safe and appropriate. Previously augmented sites were found to be more likely to require further augmentation at implant placement.